Permeability During Magma Expansion and Compaction. Issue 12 (26th December 2017) - Gonnermann, Helge. M.; Giachetti, Thomas; Fliedner, Céline; Nguyen, Chinh T.; Houghton, Bruce F.; Crozier, Joshua A.; Carey, Rebecca J.
Abstract: Plinian lapilli from the 1060 Common Era Glass Mountain rhyolitic eruption of Medicine Lake Volcano, California, were collected and analyzed for vesicularity and permeability. A subset of the samples were deformed at a temperature of 975°, under shear and normal stress, and postdeformation porosities and permeabilities were measured. Almost all undeformed samples fall within a narrow range of vesicularity (0.7–0.9), encompassing permeabilities between approximately 10 −15  m 2 and 10 −10  m 2 . A percolation threshold of approximately 0.7 is required to fit the data by a power law, whereas a percolation threshold of approximately 0.5 is estimated by fitting connected and total vesicularity using percolation modeling. The Glass Mountain samples completely overlap with a range of explosively erupted silicic samples, and it remains unclear whether the erupting magmas became permeable at porosities of approximately 0.7 or at lower values. Sample deformation resulted in compaction and vesicle connectivity either increased or decreased. At small strains permeability of some samples increased, but at higher strains permeability decreased. Samples remain permeable down to vesicularities of less than 0.2, consistent with a potential hysteresis in permeability‐porosity between expansion (vesiculation) and compaction (outgassing). We attribute this to retention of vesicle interconnectivity, albeit at reduced vesicle size, as well as bubble coalescence during shear deformation. We provide an equation that approximates the change in permeability during compaction. Based on a comparison with data from effusively erupted silicic samples, we propose that this equation can be used to model the change in permeability during compaction of effusively erupting magmas. Key Points: Magma permeability is hysteretic Change in magma permeability upon compaction is determined experimentally An equation for the change in permeability during magma compaction is proposed